FRI0286 Burden of the disease in axial spondyloarthritis. (23rd January 2014) - Sieper, J.; Rao, S.A.; Chen, N.; Cifaldi, M.A.
Abstract : Background: Axial spondyloarthritis (axSpA) is a new classification that includes ankylosing spondylitis (AS) and nonradiographic axSpA (nr-axSpA). Little is known about the severity and progressive nature of nr-axSpA relative to AS. An analysis of the German Spondyloarthritis Inception Cohort (GESPIC) indicated that clinical manifestations and disease activity measures are highly comparable between nr-axSpA and early AS. 1 We analyzed data from Phase III clinical trials of adalimumab in patients with AS and nr-axSpA compared to the results from the GESPIC study. Objectives: To compare the burden of disease experienced by patients with nr-axSpA to that of AS patients with similar disease duration and AS patients with differing disease duration. Methods: Baseline data from the ATLAS (N=315) and ABILITY-1 (N=185) trials were used. These were both Phase III trials to evaluate the safety and efficacy of adalimumab in the treatment of moderate to severe AS and nr-axSpA, respectively. Three cohorts were established: those with nr-axSpA ≤5 years' duration, established AS ≤5 years' duration, and AS >5 years' duration. Clinical impairment, pain, and physical function were measured using the Bath AS Disease Activity Index (BASDAI), total back pain (TBP) VAS, Patient's Global Assessment (PGA), and Bath AS Functional Index (BASFI) scales. Spinal mobility was assessed with the Bath AS Metrology Index (BASMI). Statistical methods included the Student t -test comparing the 2 groups with baseline scores. P -values <.05 were considered significant. Results: AS patients with longer disease duration were older and had significantly less mobility than those with a shorter disease duration (BASMI 4.3 vs. 3.3, P <.001). In early disease, nr-axSpA patients had similar clinical impairment, pain, and global scores but better mobility relative to AS patients (BASMI 1.8 vs. 3.3; P <.001). In contrast to results from the GESPIC study, physical function as measured by the BASFI scale was not significantly different between the groups. However, the populations in the ATLAS and ABILITY-1 studies had substantially more severe baseline functional impairment (BASFI 5.1 and 4.8 for AS and nr-axSpA, respectively) than that of the GESPIC (3.1 and 2.5 for AS and nr-axSpA, respectively) cohorts, indicating a more active group of patients. BASMI is the only measure that appeared to increase with disease duration (table ). Conclusions: AS and nr-axSpA patients experienced a similar burden of disease with a relatively high degree of clinical and functional impairment. Impairment of spinal mobility, as measured by BASMI, appears to be progressive, with less involvement in nr-axSpA, more involvement in AS, and a clear increase over time. Therefore, BASMI potentially could be an indicator of progression in nr-axSpA. References: Rudwaleit M. Arthritis Rheum. 2009;60:717–27. Disclosure of Interest: J. Sieper Grant/Research support from: Abbott, Consultant for: Abbott, Speakers Bureau: Abbott, S. Rao Shareholder of: Abbott, Employee of: Abbott, N. Chen Shareholder of: Abbott, Employee of: Abbott, M. Cifaldi Shareholder of: Abbott, Employee of: Abbott